Models and Targets for the Pronunciation of English in Vietnam and Sweden - Cunningham, Una (Research in Language, 2009)
This paper aims to account for the factors that lie behind the choice of models and targets for the pronunciation of English by learners of English in Vietnam and in Sweden. English is the first foreign language in both Vietnam and in Sweden. English is used as a language of international communication in both settings. Swedish learners have much more exposure to spoken English than do Vietnamese learners and the Swedish language is more similar to English than is Vietnamese. These reasons, among others, explain why Swedish accents of English are typically considerably more intelligible than Vietnamese accents of English. Given that the majority of English speakers in the world are not native speakers, it is argued that the traditional learner target of approaching native speaker pronunciations is not appropriate for either group, but especially not for the Vietnamese learners. Instead maximal international intelligibility is a more useful target. To this end, learners need to be exposed to a variety of native and non-native models.